(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Coal auger mining is a promising technology used for excavating thin coal seams. The efficiency of auger mining is largely related to the stability of mine roadways in the influence zone of the coal-face. Roof bolting systems are promising in such conditions. An adequate choice of roof bolting parameters is only possible if one understands the features of the stratification of the rocks and stages of deformation of the array in auger mining. Modern monitoring methods of the condition of rocks are based on the use of mechanical benchmarks, sounding of the mine array and the use of optical devices. There are few studies concerning roadways with auger mining. The innovations presented in this manuscript are a determination of the research results of the in-situ processes of rock deformation around a roadway in auger mining which will help to better understand the features of deformation processes in the technological method and design an adequate support system. Some field studies were undertaken in order to investigate the geo-mechanical processes that can be observed while auger mining a roadway with fully grouted bolts of 2.4 m in length. The research included monitoring rock stratification with the help of mechanical telltales, the convergence in the roadway using contour benchmarks, measurements of altitude and rock falls, and visual observations. The presented results show that roof-bolting can be used to support the roadways for auger mining.